2012
DOI: 10.1002/mus.23429
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependency of human muscle velocity recovery cycles

Abstract: Knowledge of temperature-induced changes of muscle VRC parameters is essential for future studies. Thus, the results of this study provide a firm basis for clinical studies with this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Because of this sensitivity of MRRP, all the MRRP values were corrected to the mean control temperature of 37.9°C before making statistical comparisons, using the relationship for the 40 control recordings (MRRP = 12.0 - 0.253.T; Pearson R  = −0.54, P  = 0.00057)). In contrast to the high sensitivity of MRRP to temperature, ESN is relatively insensitive to temperature changes ( R  = 0.225, P  = 0.17) as found previously [23]. …”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Because of this sensitivity of MRRP, all the MRRP values were corrected to the mean control temperature of 37.9°C before making statistical comparisons, using the relationship for the 40 control recordings (MRRP = 12.0 - 0.253.T; Pearson R  = −0.54, P  = 0.00057)). In contrast to the high sensitivity of MRRP to temperature, ESN is relatively insensitive to temperature changes ( R  = 0.225, P  = 0.17) as found previously [23]. …”
Section: Methodssupporting
confidence: 76%
“…There is a known significant dependency of MRRP measurements on body muscle temperature, which varied from 36.3 to 39.8°C in the control pigs and from 33.8°C to 39.7°C in the peritonitis group [23]. Because of this sensitivity of MRRP, all the MRRP values were corrected to the mean control temperature of 37.9°C before making statistical comparisons, using the relationship for the 40 control recordings (MRRP = 12.0 - 0.253.T; Pearson R  = −0.54, P  = 0.00057)).…”
Section: Methodsmentioning
confidence: 99%
“…Temperature has been found to affect muscle excitability parameters, with lower temperatures leading to prolongation of the MRRP . In our study cohort, no confounding relationship was observed between age and skin temperature at the recording site for any of the significant relationships reported, despite correction for this variable, as detailed previously.…”
Section: Discussionsupporting
confidence: 75%
“…The overlap of the MVRCs following single stimuli in Figure A suggest that resting potentials were similar in the 3 groups, and this is supported by the similar values of relative refractory period (MRRP) in Table . MRRP is affected by temperature, so it is important to note that skin temperatures overlying the muscle were closely matched between groups (NC 29.9 ± 1.2°C, DM1 30.0 ± 1.3°C, DM2 30.4 ± 0.6°C).…”
Section: Resultsmentioning
confidence: 97%